Pengaruh Bermain Project Dengan Media Wood Puzzle Terhadap Kemampuan Interaksi Sosial Anak Gangguan Pemusatan Perhatian Dan Hiperaktivitas (GPPH) - Fika, Nur syafika Amelia; Parwoto, Parwoto; Hajerah, Hajerah; Rusliana, Faradillah (Jurnal Kajian Anak (J-Sanak), 2025)
This study aims to analyze the effect of project-based play activities using wood puzzles on the social interaction skills of children with Attention Deficit and Hyperactivity Disorder (ADHD) at Zivana Montessori Inclusive Kindergarten in Makassar City. A quantitative approach with a single-subject experimental design (A–B–A pattern) was employed, involving a 5-year-7-month-old child who exhibited difficulties in focus, self-control, and social interaction. Data were collected through observation, documentation, and interviews, then analyzed visually and descriptively. The results revealed a significant improvement in the child’s social interaction skills following the implementation of project-based play using wood puzzles. Increases were observed in three key indicators: maintaining eye contact, engaging in cooperative play with peers, and following play rules. The average level of social interaction improved by 39% from the baseline condition, with a stable trend maintained into the post-intervention phase. The project-based play activity effectively helped the child enhance attention, cooperation, and impulse control through concrete and enjoyable learning experiences. These findings confirm that project-based play using wood puzzles is an effective strategy in inclusive early childhood education, as it fosters children’s social skills while creating a collaborative, adaptive, and meaningful learning environment.